2006
DOI: 10.1002/jemt.20357
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of changes in optical fibers during arc‐fusion splicing by use of quantitative phase imaging

Abstract: A non-interferometric imaging technique in conjunction with Abel inversion is used to directly and quantitatively examine the changes in optical fibers due to the heating produced during arc-fusion splicing as a function of fusion arc parameters. Phase images in the vicinity of a fusion splice are obtained using Quantitative Phase Microscopy, allowing the refractive-index change to be reconstructed with high spatial resolution. This simple, nondestructive method confirms that, for a fixed arc current, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Accurate quantification of the refractive index distribution using nondestructive methods is essential in modeling and designing the performance behavior of optical fiber devices including improving their fabrication process (Anemogiannis et al, 2003;Dossou et al, 2002;). This remains an area of active research, as evidenced by the large number of articles published recently on this topic Colomb et al, 2005;Dragomir et al, 2005Dragomir et al, , 2006aDü rr et al, 2005;El-Diasty, 2004;Roberts et al, 2002;Yablon, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate quantification of the refractive index distribution using nondestructive methods is essential in modeling and designing the performance behavior of optical fiber devices including improving their fabrication process (Anemogiannis et al, 2003;Dossou et al, 2002;). This remains an area of active research, as evidenced by the large number of articles published recently on this topic Colomb et al, 2005;Dragomir et al, 2005Dragomir et al, , 2006aDü rr et al, 2005;El-Diasty, 2004;Roberts et al, 2002;Yablon, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of QPM to produce simultaneous, decoupled information about the absorption and phase (Barone‐Nugent et al, 2002) has been demonstrated. Additionally, QPM has also been previously demonstrated for isotropic (Cody et al, 2005; Curl et al, 2006; Dragomir et al, 2006a) and birefringent specimens (Dragomir et al, 2006b; Dragomir et al, 2007; Roberts et al, 2002). Its potential for three‐dimensional imaging has been explored and demonstrated for specific optical devices (Dragomir et al, 2008).…”
Section: Methodsmentioning
confidence: 77%
“…As a test specimen, we chose a commercially available optical fiber (Corning Multimode (MM) graded‐index 62.5/125 μm core/cladding diameter) for testing the accuracy of the method illustrated here. An optical fiber was chosen because of its well‐known geometry (Dragomir et al, 2006a; Dragomir et al, 2008) and characteristic retardation properties (Roberts et al, 2002). Two different orientations of the fiber with respect to the microscope stage were considered to verify the accuracy of the method.…”
Section: Methodsmentioning
confidence: 99%
“…This non-invasive method for imaging transparent structures has been demonstrated for both thick [8] and thin [6]; biological [9] and inorganic [10] specimens. It can be used with partially coherent light in a conventional bright field microscope to uniquely determine the phase shift introduced into an optical wavefield by a transparent specimen.…”
Section: Quantitative Phase Microscopy: a Non-interferometric Approachmentioning
confidence: 99%